Why Are U.S. Stocks More Volatile? - BARTRAM, SÖHNKE M.; BROWN, GREGORY; STULZ, RENÉ M. (Journal of Finance, 2012)
ABSTRACT U.S. stocks are more volatile than stocks of similar foreign firms. A firm's stock return volatility can be higher for reasons that contribute positively (good volatility) or negatively (bad volatility) to shareholder wealth and economic growth. We find that the volatility of U.S. firms is higher mostly because of good volatility. Specifically, stock volatility is higher in the United States because it increases with investor protection, stock market development, new patents, and firm‐level investment in R&D. Each of these factors is related to better growth opportunities for firms and better ability to take advantage of these opportunities.